Lysosomal Acid Lipase Deficiency: Therapeutic Options - Pastores GM; Hughes DA (Dove Medical Press, 2020)
Gregory M Pastores,1 Derralynn A Hughes2 1Department of Medicine (Genetics)/National Centre for Inherited Metabolic Disorders, Mater Misericordiae University Hospital and University College Dublin, Dublin, Ireland; 2Royal Free London NHS Foundation Trust, University College London, London NW3 2QG, UKCorrespondence: Gregory M PastoresNational Centre for Inherited Metabolic Disorders, Mater Misericordiae University Hospital and University College Dublin, Dublin, IrelandTel +353 1 803 4878Fax +353 1 803 4876Email gpastores@mater.ieAbstract: Lysosomal acid lipase (LAL) deficiency is a metabolic (storage) disorder, encompassing a severe (Wolman disease) and attenuated (Cholesterol ester storage disease) subtype; both inherited as autosomal recessive traits. Cardinal clinical features include the combination of hepatic dysfunction and dyslipidemia, as a consequence of cholesteryl esters and triglyceride accumulation, predominately in the liver and vascular and reticuloendothelial system. Significant morbidity can arise, due to liver failure and/or atherosclerosis; in part related to the severity of the underlying gene defect and corresponding enzyme deficiency. Diagnosis is based on demonstration of decreased LAL enzyme activity, complemented by analysis of the cognate gene defects. Therapeutic options include dietary manipulation and the use of lipid-lowering drugs. Sebelipase alfa, a recombinant enzyme replacement therapy, has garnered regulatory approval, following demonstration of improvements in disease-relevant markers and clinical benefit in clinical trials, which included increased survival in the most severe cases.Keywords: atherosclerosis, dyslipidemia, enzyme replacement therapy, hepatomegaly, lipid-lowering medications, lysosomal acid lipase deficiency, lysosomal storage disease